Living Alongside the Threat of Eruption: Assessing the Psychosocial Capacity of Communities Affected by the Semeru Eruption - Shinta Novia Vera; Adjie Pamungkas (Jurnal Penataan Ruang, 2025)
Natural disasters pose a tangible threat that disrupts societal order, strains social systems, and leads to long-term psychological consequences. The communities living around Mount Semeru, who have coexisted with the constant risk of volcanic eruptions, present a compelling and important subject for study. This research aims to examine the post-eruption conditions of these communities and assess their level of psychosocial capacity, along with the contribution of various influencing factors. Psychosocial capacity was evaluated based on nineteen selected factors. Data collection was conducted through structured interviews with one hundred respondents from Supiturang and Sumberwuluh Villages in Lumajang Regency. Descriptive statistical analysis was employed to assess psychosocial capacity and to review the contribution of each factor in shaping the community’s overall resilience. The findings reveal that the community continues to experience post-traumatic disturbances and faces challenges in returning to normal life. The assessment results indicate that the psychosocial capacity of the community is at a moderate level, with a score of 0.542. Enhancing this capacity can be achieved through targeted interventions in several underperforming areas, including trauma recovery programs, disaster exposure experience, disaster education services, knowledge of eruption risks, and both self-efficacy and collective efficacy. This study is expected to contribute to the planning of sustainable post-eruption recovery strategies by integrating efforts to strengthen the psychosocial capacity of affected communities.